2023
DOI: 10.3390/healthcare11101410
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Shift Work and Night Work: A Literature Review

Abstract: Nonstandard work schedules such as shift work and night work tend to trigger problems for workers in different areas. To illustrate the diversity of areas affected and the relative interest of the scientific community, we conducted a literature review of the effects of shift work and night work on workers. In particular, we intended to identify the main variables addressed in the field of health, the family sphere, and the organizational context. The literature review was carried out using the Web of Science w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 159 publications
(137 reference statements)
0
4
0
2
Order By: Relevance
“…Dopamine was the strongest biomarker with a prolonged attenuation during and following a 24 hS. This finding adds novel consequences of shift work that represents variety of impacts on the worker’s physical and psychological health, covering sleep disturbance, cardiovascular diseases, metabolic system perturbations, reproductive function decrease, oncological problems, or anxious and depressive symptoms 18 .…”
Section: Discussionmentioning
confidence: 72%
“…Dopamine was the strongest biomarker with a prolonged attenuation during and following a 24 hS. This finding adds novel consequences of shift work that represents variety of impacts on the worker’s physical and psychological health, covering sleep disturbance, cardiovascular diseases, metabolic system perturbations, reproductive function decrease, oncological problems, or anxious and depressive symptoms 18 .…”
Section: Discussionmentioning
confidence: 72%
“…Other studies have found no significant sex differences concerning police officers’ quality of life ( 48–51 , 56 , 57 ). However, research on police officers’ quality of life is only recently emerging ( 50–52 , 58 ). The emphasis on job burnout prevention by the state authorities and workers in the EU shows that burnout syndrome is a problem that confers an economic burden ( 53 ); in the context of employee’s effectivity and health, it has to be dealt with.…”
Section: Discussionmentioning
confidence: 99%
“…Os autores discutem que turnos longos não são a única variável negativa. Jornadas de trabalho que se estendem em finais de semana, feriados em geral e datas festivas repercutem negativamente nas relações sociais, familiares e conjugais dos trabalhadores, fragilizando dimensões importantes de sua vida (20) .…”
Section: Discussionunclassified